ANALISIS ASUHAN KEPERAWATAN INTERVENSI TEKNIK PERNAFASAN BUTEYKO UNTUK MEMPERBAIKI FREKUENSI PERNAFASAN DAN SATURASI OKSIGEN PADA PASIEN DENGAN ASMA DI RUANG INSTALASI GAWAT DARURAT RSUD PASAR MINGGU - Fatimah Az-Zahra (2023)
Asthma is an inflammatory disease of the respiratory tract that has characteristic symptoms in the form of shortness of breath and it is signed by narrowing of the airway. Asthma becomes a disease with emergency condition that can threat life if it is not immediately resolved. The implementation of this activity is to analyze the effectiveness of the buteyko breathing technique innovation intervention on improving the respiratory frequency and oxygen saturation values of patients with asthma in the Emergency Room of Pasar Minggu Hospital. After applying the innovation intervention twice while the patient was in the emergency room, there was a better progress in respiratory status. Where there is a decrease of 4 times/minute in the respiratory frequency value and there is an increase of 3% in the oxygen saturation value. Based on the analysis that has been done, it can be concluded that buteyko breathing technique therapy is effective in providing a better progress in the respiratory frequency and oxygen saturation status of patients with asthma.